Results of conducting the primary seed production using the method of electrophoresis in the FSBSI “ARC “Donskoy - T. I. Firsova; M. M. Kopus; Yu. G. Skvortsova; G. A. Filenko (Зерновое хозяйство России, 2022)
The current paper has presented the study and estimation results of winter bread wheat varieties in primary seed production (2019-2021) based on the method of electrophoresis. In order to maintain varietal purity in different varieties there were used different methods of primary seed production. The main method was the method of laying down the plots (a field testing method) for testing progeny with a two-year estimation of families according to progeny (PIP-1 and PIP-2). In laboratory conditions, there was used the method of electrophoresis, where there was studied the polymorphism of wheat gliadin reserve proteins. The purpose of the study was to estimate the efficiency of the method of electrophoresis on reserve proteins, to develop varietal purity and belonging of winter wheat seeds to the variety in primary seed production. On the basis of the conducted study, there was found that for winter bread wheat varieties there was possible to change the biotype composition from heterogeneous to monomorphic in PIP-1 by selecting families according to morphological traits (a field testing method), and the introduction of the method of electrophoresis into seed production made it possible not only to identify varieties on changes in the biotype gliadin composition in the varieties, but also to track the ratio in which it was necessary to purposefully preserve families in primary seed production, excluding monomorphism in heterogeneous varieties. All varieties were characterized by an individual set of gliadin-coding loci, which allowed using electrophoresis on reserve proteins to identify any variety and its varietal purity.